Understanding coach burnout and underlying emotions: a narrative approach - McNeill, K.; Durand-Bush, N.; Lemyre, P.-N. (Sports Coaching Review, 2017)
The purpose of this study was to investigate coaches` subjective experiences of burnout in order to shed light on the complex emotional nature of this syndrome. Five full-time paid coaches (two women and three men) experiencing burnout participated in an in-depth individual interview as part of a larger 13-week intervention study. A content analysis of the interview data resulted in the construction of five non-fictional short stories highlighting the emotions underlying the coaches` experiences of burnout. The coaches described a variety of emotions including anxiety, anger, apathy and dejection, which had negative implications upon their well-being and coaching practice. Emotions were linked to the three dimensions of burnout; that is, emotional exhaustion, depersonalisation and reduced personal accomplishment. Findings support calls for intervention research to help coaches manage their emotions and prevent burnout.